Strategi Pembelajaran Agama Islam Berbasis PAIKEM - Karmila, Karmila; Rudi Hartono; Dadang Sumarna (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2026)
This study aims to examine the learning strategy of Islamic Religious Education (PAI) based on PAIKEM (Active, Innovative, Creative, Effective, and Enjoyable Learning) through a literature study approach. PAIKEM is a learning approach that positions students as active subjects in the learning process, thereby increasing student engagement, understanding, and learning outcomes. The method used is a literature study by reviewing various scientific sources such as journals, books, and previous research results relevant to the application of PAIKEM in PAI learning. The results of the study indicate that the application of PAIKEM in PAI learning can increase student learning motivation, strengthen understanding of religious concepts, and develop critical and creative thinking skills. In addition, this strategy also encourages teachers to be more innovative in designing contextual and meaningful learning. Other findings indicate that the use of discussion methods, educational games, digital media, and project-based learning are important parts of PAIKEM implementation. However, there are several challenges such as limited teacher competency, infrastructure, and time management in learning. Therefore, teacher training and policy support are needed to optimize the application of PAIKEM in PAI learning. Thus, PAIKEM-based learning strategies can be an effective solution for improving the quality of Islamic Religious Education (ISE) in schools.